Silver Russel syndrome in an Aboriginal patient from Australia - Poulton, C.; Azmanov, D.; Atkinson, V.; Beilby, J.; Ewans, L.; Gration, D.; Dreyer, L.; Shetty, V.; Peake, C.; McCormack, E.; Palmer, Richard; Lewis, B.; et al. (WILEY, 2018)
Silver-Russell syndrome (SRS OMIM 180860) is a rare, albeit well-recognized disorder characterized by severe intrauterine and postnatal growth retardation. It remains a clinical diagnosis with a molecular cause identifiable in approximately 60%–70% of patients. We report a 4-year-old Australian Aboriginal girl who was born at 32 weeks gestation with features strongly suggestive of SRS, after extensive investigation she was referred to our undiagnosed disease program (UDP). Genomic sequencing was performed which identified a heterozygous splice site variant in IGF2 which is predicted to be pathogenic by in-silico studies, paternal allelic origin, de novo status, and RNA studies on fibroblasts. We compare clinical findings with reported patients to add to the knowledge base on IGF2 variants and to promote the engagement of other Australian Aboriginal families in genomic medicine.